2013
DOI: 10.1007/s00203-013-0938-y
|View full text |Cite
|
Sign up to set email alerts
|

The mannobiose-forming exo-mannanase involved in a new mannan catabolic pathway in Bacteroides fragilis

Abstract: We have proposed a new mannan catabolic pathway in Bacteroides fragilis NCTC 9343 that involves a putative mannanase ManA in glycoside hydrolase family 26 (BF0771), a mannobiose and/or sugar transporter (BF0773), mannobiose 2-epimerase (BF0774), and mannosylglucose phosphorylase (BF0772). If this hypothesis is correct, ManA has to generate mannobiose from mannans as the major end product. In this study, the BF0771 gene from the B. fragilis genome was cloned and expressed in Escherichia coli cells. The expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…The relatively low specific activity of Bo Man26B is comparable with at least some other β-mannanases (30, 31, 44), yet it is 10-fold lower than for Bo Man26A. It may be hypothesized that this comparably low specific activity for galactomannan for Bo Man26B potentially could be compensated for by the mannan-binding proteins (supplemental Fig.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The relatively low specific activity of Bo Man26B is comparable with at least some other β-mannanases (30, 31, 44), yet it is 10-fold lower than for Bo Man26A. It may be hypothesized that this comparably low specific activity for galactomannan for Bo Man26B potentially could be compensated for by the mannan-binding proteins (supplemental Fig.…”
Section: Discussionmentioning
confidence: 87%
“…It has the highest sequence identity (66%) to Bf Man26, a GH26 β-mannanase from Bacteroides fragilis (31). A 3D structure of Bo Man26A was obtained using molecular replacement with the structure of GH26 mannanase C from Cellvibrio japonicus ( Cj Man26C), the closest homologue with a solved structure (23).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we showed that the gene for BfCE (locus tag BF0774) is located on an operon (locus tags from BF0771 to BF0774) in the B. fragilis NCTC 9343 genome (NC_003228) (Senoura et al 2011). We demonstrated that the BF0771 gene product was a mannobiose-forming exo-mannanase belonging to glycoside hydrolase family 26 (Kawaguchi et al 2014). We also showed that the physiological function of BfCE was the conversion of true substrate mannobiose to Man-Glc and concluded that the enzyme should be named mannobiose 2-epimerase (MBE).…”
Section: Discussionmentioning
confidence: 96%
“…After incubation for 5 min, the reaction was terminated by adding 50 μL of 1 N NaOH. The amounts of product formed were determined by highperformance anion-exchange chromatography with a pulsed amperometric detection system and a CarboPac PA1 column (4 mm×250 mm) (Dionex, Sunnyvale, CA) (Kawaguchi et al 2014). Elution was performed using 10 mM NaOH spiked with 2 mM barium acetate at a flow rate of 1.0 mL/min.…”
Section: Enzyme Assaysmentioning
confidence: 99%